The Role of the Principal in Croatian Education: Manager, Leader or Administrator - Burcar, Željko (European Journal of Mental Health, 2014)
Manager, Leader or Administrator: The purpose of this study is to examine problems in the fields of educational management and instructional leadership in Croatia that could serve as possible starting points for future studies or research. This study examines the role of the school principal within the context of modern-day schooling in turbulent surroundings, growing responsibility and overloaded schedule. According to findings we can explain eight different roles principals perform in Croatian education: a) information collector and disseminator, b) communicator, c) strategist and planner, d) executive manager, administrator and organiser, e) educational leader and educator, f) evaluator, g) student and h) community liaison. The principal’s roles are oriented toward: a) people, b) tasks/goals, c) school as organisation, and d) processes inside the school. Tasks generated from such orientation belong to an ideal administrative process: planning, decision-making, organising, coordination, communication, influence and evaluation effective in five tasks of school management: school program, pupils, staff, and relations with community, physical preconditions, and management.